The influence of eco-label knowledge and trust on pro-environmental consumer behaviour in an emerging market - Taufique, Khan Md Raziuddin; Vocino, Andrea; Polonsky, Michael Jay (© 2016 Informa UK Limited, trading as Taylor & Francis Group., 2018)
This article was published in the Journal of Strategic Marketing [© 2016 Informa UK Limited, trading as Taylor & Francis Group.] and the definite version is available at: http://doi.org/10.1080/0965254X.2016.1240219. The Article's website is at: http://www.tandfonline.com/doi/full/10.1080/0965254X.2016.1240219